Enhancing Meaningful Participation in the Law-Making Process in Indonesia: A Comparative Review - Antari, Putu Eva Ditayani; Fadli, Moh.; Negara, Tunggul Anshari Setia; Susmayanti, Riana; Putri, Luh Putu Yeyen Karista (UNISSULA, 2025)
Public participation in forming laws shows variations in their application in Indonesia, the United States and the Netherlands. To find out about the urgency and implementation of public participation in the formation of laws and regulations, normative legal research is carried out based on the legal materials that have been collected. The legal material used is primary legal material related to statutory regulations governing the mechanism for forming statutory regulations. While the secondary legal materials used mainly come from scientific articles published in journals, which discuss popular sovereignty, democracy, community participation, and the mechanisms for forming legislation in various countries. The study results show that the urgency of public participation in the formation of laws and regulations is needed to carry out the teachings of people's sovereignty and democracy in a state, where the highest power lies with the people. Therefore, the people must be involved in forming laws as the legitimacy of government policies. The form of public participation in the formation of laws and regulations in Indonesia is carried out at the stages of preparing academic papers and discussing draft laws and regulations, either through direct participation or representatives.